2018
DOI: 10.1016/j.rgg.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene biomarkers in the organic matter of Precambrian and Phanerozoic deposits and in the oils of the Siberian Platform

Abstract: The composition and distribution of phenanthrenes (polyaromatic compounds) have been studied in chloroform extracts from dispersed organic matter (OM) of clayey, siliceous, carbonate, and terrigenous rocks of different ages and facies and from some oils of the Siberian Platform. Phenanthrenes have been analyzed by gas chromatography–mass spectrometry. High contents of 1,7,8-trimethylphenanthrene and 1,1,7,8-tetramethyl-1,2,3,4-tetrahydrophenanthrene are present in the OM of Vendian and Cambrian carbonate-shale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…or steeply-dipping faults, into the overlying Upper Vendian and Lower Cambrian. Biomarker evidence published by Kashirtsev et al (1999) is consistent with all of the Riphean to Early Cambrian oils of the Nepa-Botuoba Anteclise having been sourced from organicrich Riphean and Vendian carbonates and calcareous mudstones deposited on the passive margin of the Siberian Platform. Drobot et al (2004) proposed that the same kitchen has been the source of gas in fields located in the Angara-Lena Step including the giant Kovykta field NW of Lake Baikal (Fig.…”
Section: Baikal-patom Kitchensupporting
confidence: 59%
See 3 more Smart Citations
“…or steeply-dipping faults, into the overlying Upper Vendian and Lower Cambrian. Biomarker evidence published by Kashirtsev et al (1999) is consistent with all of the Riphean to Early Cambrian oils of the Nepa-Botuoba Anteclise having been sourced from organicrich Riphean and Vendian carbonates and calcareous mudstones deposited on the passive margin of the Siberian Platform. Drobot et al (2004) proposed that the same kitchen has been the source of gas in fields located in the Angara-Lena Step including the giant Kovykta field NW of Lake Baikal (Fig.…”
Section: Baikal-patom Kitchensupporting
confidence: 59%
“…Starosel 'tsev et al (2013) stated that Llandoverian (Lower Silurian) graptolite shales in Eastern Siberia display elevated contents of organic matter and form potential source rocks, although there is little information on their nature or distribution. Devonian source rocks do not appear to be widespread, but biomarker evidence published by Kashirtsev et al (1999) indicates that oils within the Permian reservoir at the South Tigyansk field on the northern flank of the Anabar Arch were generated by source rocks deposited in a hypersaline environment, consistent with the Devonian of the Lena-Anabar Basin to the north. Coals and carbonaceous mudrocks of Late Carboniferous to Permian age form widespread gas-prone source rocks across the Siberian Platform, including the Vilyui and Tunguska Basins.…”
Section: Post-riphean Source Rocksmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of naphthalene is higher in shale oil from the Domanic rocks of the Berezovskaya area, in contrast to the oil from carbonate rocks of the Zelenogorskaya area (25.14 vs. 18.01%). In [61], the possible ways of phenanthrene formation-biomarkers in OM of rocks and crude oils-are discussed. It is shown that such molecules can play a role of "secondary" biomarkers in shale oils generated by dispersed organic matter of different facies and ages.…”
Section: Zelenogorskaya Area Berezovskaya Areamentioning
confidence: 99%